ANALISA KEBIJAKAN RESPONSIF GENDER DI LINGKUNGAN PERGURUAN TINGGI (STUDI KASUS DOSEN DAN TENAGA KEPENDIDIKAN UPN VETERAN JAWA TIMUR) - Januari Pratama Nurratri Trisnaningtyas; Firsty Chintya Laksmi Perbawani (Journal Publicuho, 2023)
The purpose of this writing is to analyze and determine Gender Responsive Policy Analysis In The Higher Education Environment (Case Study Of Upn Veteran East Java Lecturer And Educational Personnel). The research method uses a mixed methods research approach with questionnaire data collection techniques and focus group discussions (FGD). The research results show that although the policies within the UPN "Veteran" East Java are quite gender-responsive, they require further attention in several sectors. By integrating the insights gained from this research, it is hoped that UPN "Veteran" East Java can take meaningful steps to create a responsive and inclusive workplace. This research contributes to the growing discourse around gender-responsive policies in the academic environment, highlighting achievements and areas for improvement for the benefit of the entire academic community, especially for lecturers and education staff